Speed-endurance test (6 x 50m)/speed test (2 x 25m) - Pyne, D.; Maw, G.; Goldsmith, W. (coachesinfo.com)
The aim of th test described is to assess the ability of the swimmer to sustain near race speed over 6 x 50m intervals. This type of broken swim is often undertaken by coaches to evaluate the 'race readiness' of swimmers through the training season, and in particular, during the final preparation prior to competition. In energetic terms, the 6 x 50m test gives an indirect estimation of the power and capacity of the anaerobic glycolytic system. This energy system is a major contributor of ATP production during maximal effort exercise of 1-3 min in duration. The protocol for the test is 6 x 50m maximal effort swims. Freestyle and form swimmers should use their preferred stroke, while individual medley swimmers should use their strongest stroke at the coaches discretion. It is recommended that a number of short sprints (25 m) at the expected speed of the 6 x 50m efforts should be undertaken in the warm-up.